UMP established a strategic collaboration with USU and AMIK Tunas Bangsa - UMP, PNC
Universiti Malaysia Pahang (UMP) inked a memorandum of understanding with Universitas Sumatera Utara (USU) that would serve as a catalyst that would add more values to the strategic alliance formed between the two universities.